Flexible Resources Key to Neighborhood Resilience for Children: A Scoping Review - Shawna Beese; Kailie Drumm; Kayla Wells-Yoakum; Julie Postma; Janessa M. Graves (MDPI AG, 2023)
Neighborhoods have been the focus of health researchers seeking to develop upstream strategies to mitigate downstream disease development. In recent years, neighborhoods have become a primary target in efforts to promote health and resilience following deleterious social conditions such as the climate crisis, extreme weather events, the global pandemic, and supply chain disruptions. Children are often the most vulnerable populations after experiencing unexpected shocks. To examine and describe conceptually the construct of Neighborhood Resilience, we conducted a comprehensive scoping review using the terms ("resilience" or "resiliency" or "resilient") AND ("neighborhood"), utilizing MEDLINE (through PubMed) and CINAHL (through EBSCOhost) databases, to assess overall neighborhood themes that impact resilience. A total of 57 articles were extracted that met inclusion criteria. Extracted characteristics included study purpose, country of origin, key findings, environmental protective/risk factors. The analysis revealed a positive relationship between neighborhood resource density, neighborhood resiliency, and individual resiliency. This study reports the finding for studies with a population focus of pre-school age and school age children (1.5-18 years of age). Broadly, we identified that the primary goals regarding neighborhood resilience for childhood can be conceptualized as all activities and resources that (a) prevent trauma during childhood development and/or (b) mitigate or heal childhood trauma once it has occurred. This goal conceptually encompasses antecedents that increase protective factors and reduces risk factors for children and their families. This comprehensive look at the literature showed that a neighborhood's ability to build, promote, and maintain resiliency is often largely dependent on the flexible resources (i.e., knowledge, money, power, prestige, and beneficial social connections) that are available.